2008
DOI: 10.1071/rd08037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oxidative stress in porcine oocytes and the role of anti-oxidants

Abstract: The mechanisms of oxidative stress in in vitro maturing porcine oocytes and the effects of anti-oxidant supplementation of the medium in ameliorating these effects were investigated in the present study. In addition to intracellular reduced glutathione (GSH) concentrations and DNA fragmentation, the present study focused on superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase activity. The anti-oxidants used were N-acetylcysteine (NAC) and its derivative NAC-amide (NACA). The results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…In order to recover GSH, oocytes use another enzyme, glutathione reductase (GSR), to reduce the GS-SG (oxidized form of GSH) back to GSH (Guerin et al 2001). Because of lower levels of GSH within in vitro matured canine oocytes (!8 pMol/oocyte) in comparison with in vivo (19.2 pMol/oocyte) (Kim et al 2007), high levels of H 2 O 2 and ROS within COCs during IVM can severely impair maturation and increase degeneration rates (Whitaker & Knight 2008). These studies showed that the H 2 O 2 level in oocytes is a good indication of oxidative stress.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In order to recover GSH, oocytes use another enzyme, glutathione reductase (GSR), to reduce the GS-SG (oxidized form of GSH) back to GSH (Guerin et al 2001). Because of lower levels of GSH within in vitro matured canine oocytes (!8 pMol/oocyte) in comparison with in vivo (19.2 pMol/oocyte) (Kim et al 2007), high levels of H 2 O 2 and ROS within COCs during IVM can severely impair maturation and increase degeneration rates (Whitaker & Knight 2008). These studies showed that the H 2 O 2 level in oocytes is a good indication of oxidative stress.…”
Section: Introductionmentioning
confidence: 76%
“…2B). It is noteworthy that H 2 O 2 is a byproduct of the ROS protection system in which SOD enzymes transform damaging oxygen-free radicals into less aggressive H 2 O 2 molecules (Whitaker & Knight 2008). As oxidative stress is introduced to oocytes immediately after mechanical extraction till the end of the culture period via various sources of free radicals, light and physical trauma (Guerin et al 2001, Menezo et al 2010, it is necessary to provide these cells with least amount of Effects of oxygen level on canine oocyte maturation stressors.…”
Section: Oxidative Stress and Ivmmentioning
confidence: 99%
See 2 more Smart Citations
“…It occurs during oocyte maturation in vitro and seems to be the motor of ovulation in vivo [Martin-Romero et al, 2008;Whitaker and Knight, 2008;Spanel-Borowski, 2011a]. It also appears that it is not the oxidative stress but rather a physiological production and action of ROS that evolves as a signaling factor to induce ovulation [Shkolnik et al, 2011].…”
Section: Introductionmentioning
confidence: 99%